Perbandingan Algoritme C4.5 and Naive Bayes untuk Mengetahui Masa Studi - Siti Nur‘Aisyah (Journal of Computer Science and Engineering (JCSE), 2020)
This research was  to make comparisons between Algorithms C4.5 and Naive Bayes which is implemented on the data of graduation of Universitas Amikom Purwokerto students from 2011 to 2013 for Strata 1, Informatics Engineering study program for the renowned study. Attributes are NIM, gender, Achievement Index Semester 1 through 6 and graduation period. The test results with both algorithms use the Selection-Based Correlation feature feature (CFS) and testing methods using Confusion Matrix. Known Algorithm C4.5 has an accuracy of 72.679% with Precision value of 0.742, Remember 0.936 and F - Measure 0.828 whereas Naive Bayes obtained an accuracy of 73.6074% with a Precision value of 0.755, Remember 0.924 and F - Measure 0.831